Hydrological modeling of reclaimed catchment area and pit lake for the management of degraded post-mining land - Triwibowo, Didik; Elma, Muthia; Suhartono, Eko; Riduan, Rony; Noor, Ihsan (Brawijaya University, 2025)
Open-pit coal mining temporarily alters natural landscapes, resulting in degraded overburden dumps and the formation of pit lakes. In Indonesia, post-mining landforms must undergo reclamation to support sustainable land use. This study evaluates the hydrological capacity of a reclaimed area functioning as the catchment for the Paringin pit lake by applying two hydrological models: the National Rural Electric Cooperative Association (NRECA) and the F.J. Mock model. Using an integrated approach that combines remote sensing, GIS-based spatial analysis, and field-based observations—including meteorological data, real-time inflow monitoring using aerial sensors, and Total Suspended Solids (TSS) measurement—both models successfully simulated monthly inflow and showed good agreement with field observations. Under a tropical climate with over 3,000 mm of annual rainfall and evaporation exceeding 1,000 mm, the catchment-to-lake area ratio of 6.4:1 was found to support sustainable inflow volumes ranging from 0.078 to 0.103 m³/s throughout the year. Although the estimated erosion rate of 3.51 t/ha/year remains within acceptable limits, average TSS levels (89.13 mg/L) exceeded the regulatory threshold of 50 mg/L for raw water supply and aquaculture use. The results affirm the effectiveness of the NRECA and F.J. Mock model in supporting post-mining water management where monitoring data are scarce. This study contributes to the growing need for hydrological connectivity assessment in post-mining landscapes and supports improved planning and sustainable management of pit lakes as integrated components of degraded post-mining land.